Implicit Groups of Web Pages as Constrained Top N Concepts - Li, A.; Haraguchi, M.; Okubo, Y. (Proceedings of the 2008 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology - Volume 03, 2008)
This paper presents an effective depth-first mining algorithm for finding relatively smaller therefore more implicit groups of Web pages as formal concepts. The algorithm is based on a dynamic ordering method depending on each search node and some search tree expansion rules. Moreover it is designed so as to find top N implicit concepts subject to the size restriction and some space constraints reflecting user’s interests.